Changes between Version 1 and Version 2 of u/johannjc/scratchpad13


Ignore:
Timestamp:
03/11/16 13:47:50 (9 years ago)
Author:
Jonathan
Comment:

Legend:

Unmodified
Added
Removed
Modified
  • u/johannjc/scratchpad13

    v1 v2  
    1717
    1818$\psi= 1 + 2 (\Xi^{-1}-1)$
     19
     20
     21== Vis-visa equation ==
     22$v = \sqrt{\mu} \sqrt{\frac{2}{r}-\frac{1}{a}}$
     23
     24$T = 2 \pi \sqrt{\frac{a^3}{\mu}}$
     25
     26$v^2=\mu(\frac{2}{r}-\frac{1}{a})$
     27
     28now since $\mu = v_k^2 r$ we have
     29
     30$v^2=v_k^2 (2 - r/a)$ which can be solved for $a$
     31
     32And the angular momentum is
     33
     34$h = r \times v$
     35
     36which can be used to solve for $e$
     37
     38$(1-e^2)=\frac{h^2}{r^2v_k^2} \frac{r}{a}$
     39
     40We can then calculate the phase using
     41
     42$l=\frac{b^2}{a}=\left ( 1-e^2 \right )a$
     43
     44$r=\frac{l}{1+e \cos \theta}$
     45
     46$\frac{r}{a} = \frac{(1-e^2)}{1+e \cos \theta}$
     47
     48$\cos{\theta}=\frac{(1-e^2)a-r}{re} $
     49
     50
     51== General case ==
     52
     53FIrst calculate the semi-major axis
     54
     55$c_s^2+v_k^2+2 c_s v_k \sin \phi = v_k^2 (2-r/a)$
     56
     57$r/a = 1 - x^2-2x \sin \phi$
     58
     59$a = \frac{r}{1-x^2-2x \sin \phi}$
     60
     61Note that this sets a limit on $x$ for material remaining elliptical...
     62
     63$x^2+2x-1=0$
     64
     65$x = \sqrt{2}-1 = .414...$
     66
     67
     68Setting $a=r$ gives us the location that launches an elliptic orbit with the same period
     69
     70$x^2+1+2x \sin \phi=2-r/a$
     71
     72$x+2 \sin \phi = 0$
     73
     74$\phi = \sin^{-1} \left ( -x / 2 \right )$
     75
     76
     77We can then calculate the ellipticity using
     78
     79$h=r v_k (1+x\sin\phi)$
     80
     81$e = \sqrt{1 - \frac{h^2}{a r v_k^2}} = \sqrt{1 - (1+x \sin \phi)^2\frac{r}{a}}$
     82
     83$e = \sqrt{1 - (1+x \sin \phi)^2 (1 - x^2-2x \sin \phi)}$
     84
     85
     86And the phase using
     87
     88$\cos{\theta}=\frac{(1-e^2)a-r}{re} $
     89
     90$\cos{\theta}=\frac{(1+x \sin \phi)^2-1}{ \sqrt{1 - (1+x \sin \phi)^2(1 - x^2-2x \sin \phi)}}$
     91
     92
     93
     94$\sin{\phi} = 1 \rightarrow e = \sqrt{1 - (1 + x)^2(1-x^2-2x)} = \sqrt{1 - ( (1 + 2x + x^2)(1 - x^2 - 2x))} = \sqrt{1 - (1 - x^2 - 2x + 2x - 2x^3 - 4x^2 + x^2 - x^4 - 2x^3)} = \sqrt{1-(1  - 4x^3 - 4x^2 - x^4 )} = \sqrt{4x^2+4x^3+x^4} = 2x+x^2$
     95
     96
     97
     98
     99
     100== parallel kick==
     101$  (c_s \pm v_k)^2 = v_k^2 (2-r/a)$
     102
     103$ (x \pm 1)^2=2-r/a $
     104
     105$ 1 \pm 2 x + x^2 = (2-r/a)$
     106
     107
     108$ \pm 2x + x^2 = 1 - r/a$
     109
     110$a = \frac{r}{1 \mp 2x - x^2}$
     111
     112$(1 \mp e)=\frac{r}{a}={1 \mp 2x - x^2}$
     113
     114$e = 2x \pm x^2$
     115
     116== orthogonal kick ==
     117$c_s^2 + v_k^2=v_k^2 (2-r/a)$
     118
     119$x^2=(1 - r/a)$
     120
     121$a = \frac{r}{1-x^2}$
     122
     123$h = r \times v = r v_k$
     124
     125$(1-e^2)=\frac{h^2}{a\mu} = \frac{r}{a}$
     126
     127$e = \sqrt{1 - \frac{r}{a}} = \sqrt{1-x^2}$
     128
     129$r=\frac{l}{1+e \cos \theta}$
     130
     131$l=\frac{b^2}{a}=\left ( 1-e^2 \right )a$
     132
     133$\frac{r}{a} = \frac{(1-e^2)}{1+e \cos \theta}$
     134
     135$\cos{\theta}=\frac{(1-e^2)a-r}{re} $
     136
     137$1-x^2=\frac{x^2}{1+\sqrt{1-x^2}\cos \theta}$
     138
     139$\cos{\theta} = \frac{\frac{x^2}{1-x^2} - 1}{\sqrt{1-x^2}}$
     140
     141$\cos{\theta} = \frac{2 x^2 - 1}{\left ( 1-x^2 \right)^{3/2}}$
     142
     143For outer edge, we are headed toward aphelion so perihelion must have $\theta$ must be between $0$ and $\pi$
     144
     145For inner edge we are headed toward perihelion, so $\theta$ must be between $\pi$ and $2 \pi$
     146
     147== Equi-period direction ==
     148
     149$c_s^2+v_k^2+2 c_s v_k \sin \phi = v_k^2 (2-r/a)$
     150
     151$x^2+1+2x \sin \phi=2-r/a$
     152
     153$x+2 \sin \phi = 0$
     154
     155$\phi = \sin^{-1} \left ( -x / 2 \right )$
     156
     157== Arbitrary direction ==
     158
     159$c_s^2+v_k^2+2 c_s v_k \sin \phi = v_k^2 (2-r/a)$
     160
     161$r/a = 1 - x^2-2x \sin \phi$
     162
     163$h=r v_k (1+x\sin\phi)$
     164
     165$e = \sqrt{1 - \frac{h^2}{a r v_k^2}} = \sqrt{1 - (1+x \sin \phi)^2\frac{r}{a}}$
     166
     167$e = \sqrt{1 - (1+x \sin \phi)^2 (1 - x^2-2x \sin \phi)}$
     168
     169
     170
     171$\sin{\phi} = 1 \rightarrow e = \sqrt{1 - (1 + x)^2(1-x^2-2x)} = \sqrt{1 - ( (1 + 2x + x^2)(1 - x^2 - 2x))} = \sqrt{1 - (1 - x^2 - 2x + 2x - 2x^3 - 4x^2 + x^2 - x^4 - 2x^3)} = \sqrt{1-(1  - 4x^3 - 4x^2 - x^4 )} = \sqrt{4x^2+4x^3+x^4} = 2x+x^2$
     172
     173